"INNOCENT PLEASURES" OF PANTELEYMON KULISH... - Sevrasevych, M. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Eugen Nahlic, Oksana Nahlic. Panteleymon Kulish between Paraska Glibov and Gorpina Nicolaev: biografic-culturel research; With addition of unknown correspondence / Monographic secret service of E.C.Nahlik; Organization, tecstologichne preparation of leaves and comments of E.C.Nahlik and O.M.Nahlik; NAN of Ukraine. Lvov separation of Institute of literature the name T.G.Shevchenko of. – L’viv, 2009. - 319 p., il. - Series the "Study studios" of literature. i.13.